Robot-assisted surface treatment strategies of AA6014 sheet metal for accumulative roll bonding - Zettl, Bastian; Merklein, Marion (ESAFORM 2021 - 24th International Conference on Material Forming, 2021)
The application of high strength aluminum sheet metal components in automotive and aviation products effectively saves material and thus weight. Material strengthening can be realized by accumulative roll bonding (ARB), which belongs to the severe plastic deformation processes. Through repeated rolling steps a multilayered sheet metal is produced, which possesses increased strength due to its ultra-fine grained microstructure. Prior to each rolling step a surface treatment via wire brushing is mandatory for removing the oxide layer and roughening the sheet surface, which enables the bonding between the unique layers during rolling. The necessary surface treatment of the sheets is not fully understood by the current state of the art. In the past, it was not possible to achieve a defined and stable surface finish, because the brushing operation was done manually. The improvement of the process stability is essential to determine the relationship between the input parameters for brushing and the resulting bond strength of multilayered ARB sheets. For this reason, a robot-controlled surface treatment is introduced. The investigated material is the precipitation-hardened aluminum AA6014 with a sheet thickness of 1 mm. A suitable brushing kinematic under constant load is implemented and its effects on the surface properties are investigated by roughness measurements. The investigation shows, that the parameter combination leads to comparable or even higher roughness values than through manual brushing. Through 16 consecutive brushing paths a homogeneous and sufficient high surface roughness is realized, which enables material bonding in the rolling step. Thus, the research results indicate, that the robot-assisted surface treatment of ARB sheet metal is a promising method for a better automation and reproducibility of the brushing and the overall ARB process.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Accumulative roll bonding; Robot-assisted brushing; Roughness; Surface treatment